Associations between Psychosocial Functioning and Academic Achievement: The Peruvian Case (2012)
The present study investigated (a) how specific aspects of psychosocial functioning (behavioral problems and global self-worth) are associated with academic achievement in spelling, arithmetic and reading; and (b) what is the effect of type of school (private vs. public) on this association. The sample for this study consisted of 901 regular school children attending 6th grade of primary education, living in the urban zones of Metropolitan Lima, Peru. Our research hypotheses were partially corroborated. The results showed a strong relationship between academic achievement and psychosocial functioning, with an important role of gender and school failure at the student level. Nevertheless, we could not confirm our multilevel assumption. There is no evidence that this relationship differs among schools. Practical implications are discussed.